The Influence of A Health Lifestyle On The Academic Performance of Third-Year Tashkent Medical Academy Students (Eurasian Scientific Herald, 2024)
A healthy lifestyle ensures human development and health. It has a beneficial effect on the physiological and mental states of students. Our research was aimed at certain influencing factors, students' performance and noncompliance with a healthy lifestyle.